PM2.5, PM10 and bronchiolitis severity: A cohort study. Issue 10 (1st October 2022) - Milani, Gregorio P.; Cafora, Marco; Favero, Chiara; Luganini, Anna; Carugno, Michele; Lenzi, Erica; Pistocchi, Anna; Pinatel, Eva; Pariota, Luigi; Ferrari, Luca; Bollati, Valentina
Abstract: Background: A few studies suggest that particulate matter (PM) exposure might play a role in bronchiolitis. However, available data are mostly focused on the risk of hospitalization and come from retrospective studies that provided conflicting results. This prospective study investigated the association between PM (PM2.5 and PM10 ) exposure and the severity of bronchiolitis. Methods: This prospective cohort study was conducted between November 2019 and February 2020 at the pediatric emergency department of the Fondazione IRCCS Ca′ Ospedale Maggiore Policlinico, Milan, Italy. Infants <1 year of age with bronchiolitis were eligible. The bronchiolitis severity score was assessed in each infant and a nasal swab was collected to detect respiratory viruses. The daily PM10 and PM2.5 exposure in the 29 preceding days were considered. Adjusted regression models were employed to evaluate the association between the severity score and PM10 and PM2.5 exposure. Results: A positive association between the PM2.5 levels and the severity score was found at day‐2 (β 0.0214, 95% CI 0.0011–0.0417, p = .0386), day‐5 (β 0.0313, 95% CI 0.0054–0.0572, p = .0179), day‐14 (β 0.0284, 95% CI 0.0078–0.0490, p = .0069), day‐15 (β 0.0496, 95% CI 0.0242–0.0750, p = .0001) and day‐16 (β 0.0327, 95% CI 0.0080–0.0574, p = .0093).Similar figures were observed considering the PM10 exposure and limiting the analyses to infants with respiratory syncytial virus. Conclusion: This study shows for the first time a direct association between PM2.5 and PM10 levels and the severity of bronchiolitis.